Multi-nested anti-resonant fiber with ice-cream-shaped tubes for terahertz communications - Xu, Xinxiu; Chen, Yanguang; Zhang, Junsheng (Frontiers in Physics, 2025)
A novel multi-nested anti-resonant fiber for reducing propagation losses in the terahertz band was proposed. The transmission properties of the fibers were analyzed using the finite element method. High-resistivity silicon was used as the fiber material, and the confinement loss of the fiber was reduced by employing eight circumferentially symmetric multi-nested ice-cream-shaped tubes. By optimizing the structural parameters of cladding tubes, the transmission loss of the fiber was effectively reduced. Simulation results show that the total loss of the designed fiber was 1.53 × 10−4 dB/m. The low loss transmission bandwidth (less than 10–3 dB/m) was 0.26 THz in the 0.6–1.4 THz range. The proposed fiber offered a new possibility for low-loss communication in the terahertz band, demonstrating huge commercial potential.